Fields and waves in communication electronics - Ramo, Simon; Whinnery, John R.; Duzer, Theodore Van (Singapore : John Wiley, 2004)
Chemistry and Physics
Keywords: Electromagnetic waves; Electromagnetic fields; Telecommunications